Design of an UNDO framework - Merlino, Hernán (2009)
This paper sets out to provide a highly automated mechanism for an undo process that can be easily built into a new or existing system. Our proposal is based on the observation that it is not necessary to store the state of objects in memory, or the commands executed by the system to perform an undo, but it is sufficient to store the input data. This greatly simplifies the design process and undo encapsulate most of the functionality into a framework similar to those existing in many object oriented programming